2014
DOI: 10.3349/ymj.2014.55.1.126
|View full text |Cite
|
Sign up to set email alerts
|

The Immunogenicity of a Single Dose of Hepatitis A Virus Vaccines (Havrix® and Epaxal®) in Korean Young Adults

Abstract: PurposeAssessing the immunogenicity of a single dose of hepatitis A virus (HAV) vaccines is important because some people receive only a single dose. However, previous studies have shown variable results and have not examined the effects of demographic characteristics other than gender. This study was performed to examine the immunogenicity of a single dose of HAV vaccine according to the vaccine type and demographic characteristics in young adults.Materials and MethodsSeronegative medical school students were… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
17
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
6
3

Relationship

1
8

Authors

Journals

citations
Cited by 29 publications
(20 citation statements)
references
References 13 publications
3
17
0
Order By: Relevance
“…When anti-HAV titers were measured four weeks post-vaccination, both weight (p=0.019) and BMI (p=0.016) were significant predictors of non-protective (anti-HAV titers < 10 mIU/mL) seroresponse, with the odds of being a responder increasing as weight and BMI decreased. However, another study showed no difference in anti-HAV titers between healthy and obese individuals, suggesting obesity may not significantly affect seroconversion after hepatitis A vaccine in some populations [45]. To our knowledge, these are the only data suggesting a poor HAV vaccine-induced immune response in obese individuals.…”
Section: Hepatitis B Virus (Hbv)mentioning
confidence: 96%
“…When anti-HAV titers were measured four weeks post-vaccination, both weight (p=0.019) and BMI (p=0.016) were significant predictors of non-protective (anti-HAV titers < 10 mIU/mL) seroresponse, with the odds of being a responder increasing as weight and BMI decreased. However, another study showed no difference in anti-HAV titers between healthy and obese individuals, suggesting obesity may not significantly affect seroconversion after hepatitis A vaccine in some populations [45]. To our knowledge, these are the only data suggesting a poor HAV vaccine-induced immune response in obese individuals.…”
Section: Hepatitis B Virus (Hbv)mentioning
confidence: 96%
“…Alcohol consumption. Alcohol intake has been found not to influence antibody responses to HepA (405) or HepB (68,69,81,402,406) vaccination but might influence responses to pneumococcus vaccination (142). After vaccination with PPV23, alcoholics have lower SCRs to serotypes 3, 4, 7F, 8, and 19F (however, this is significant only for serotypes 3 and 19F) (142) (Table 13).…”
Section: Behavioral Factorsmentioning
confidence: 97%
“…Similar to our previous study [ 2 ], the current study was executed in the following eight medical schools located throughout the country: Eulji University, Kwandong University, Inje University, Konyang University, Keimyung University, Yonsei Wonju University, Soonchunhyang University, and Wonkwang University. Participants were enrolled and vaccinated from November 4, 2010 to April 7, 2011, and they were followed up from November 16, 2012 to December 14, 2012.…”
Section: Methodsmentioning
confidence: 99%
“…In our previous study, we found that immunogenicity differed according to the vaccine type only among men (81.9% vs. 69.2% in the Havrix and Epaxal groups, respectively), whereas the immunogenicity of both vaccines was similarly high among women (90.1% vs. 92.9% in the Havrix and Epaxal groups, respectively) [ 2 ]. This gender-vaccine type interaction has a clinical significance because if Epaxal consistently shows lower immunogenicity particularly in men, Havrix rather than Epaxal should be administered to men.…”
Section: Introductionmentioning
confidence: 99%